NR2F2 regulation of interstitial cell fate in the embryonic mouse testis and its impact on differences of sex development - Martín Andrés Estermann; Sara A. Grimm; Abigail S. Kitakule; Karina F. Rodriguez; Paula R. Brown; Kathryn McClelland; Ciro M. Amato; Humphrey Hung-Chang Yao (Nature Communications)
Abstract Testicular fetal Leydig cells produce androgens essential for male reproductive development. Impaired fetal Leydig cell differentiation leads to differences of sex development including hypospadias, cryptorchidism, and infertility. Despite fetal Leydig cells are thought to originate from proliferating progenitor cells in the testis interstitium, the precise mechanisms governing the interstitial cells to fetal Leydig cell transition remain elusive. Using mouse models and single-nucleus multiomics, we find that fetal Leydig cells arise from a Nr2f2-positive interstitial population. Embryonic deletion of Nr2f2 in mouse testes results in differences of sex development, including dysgenic testes, Leydig cell hypoplasia, cryptorchidism, and hypospadias. By combining single-nucleus multiomics and NR2F2 ChIP-seq we find that NR2F2 promotes the progenitor fate while suppresses Leydig cell differentiation by modulating key transcription factors and downstream genes. Our findings establish Nr2f2 as a crucial regulator of fetal Leydig cell differentiation and provide molecular insights into differences of sex development linked to Nr2f2 mutations.